Phonological Differences of Persian Loan Words in Arabic - Mokhalad Naji Kamil; Yadollah Mansouri; Zeinab Mohammad Ebrahimi (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The purpose of the research is to study the phonological mutations of Persian loanwords in Arabic , on the focus of the Phonological processes . Speakers of any language use the loan word , and They change in their native morphological and phonological system. Authors gathered 300 Persian loan words which are originated from Persian language then he extracts phonetic forms and phonological differences of these words from two languages. The framework of the study is OT (Optimality Theory). The current study attempts to diagnose linguistically systematic phonological changes and provide a typology for classifying them. The findings of the study are that interdentally, pharyngeal, and bilabial glide places of articulation are inactive articulators in Persian and Persian language speakers replace loan words containing these consonants with the closest consonants in terms of place of articulation. The aim of this study is to investigate phonological and phonetic changes in both languages. In this research, first lexical Which has been specified from Persian and Arabic languages, then Study of phonological changes such as phonological stress , change, insertion, deletion, Softening, and metathesis are discussed .In this research, descriptive and analytical methods used to collect data.